PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT LIHE AUTO PARTS INDONESIA CIKARANG PUSAT - Febrina Kumala Putri; Rian Sri Rahayu (Journal of Research and Publication Innovation, 2025)
discipline both partially and simultaneously on employee performance at PT Lihe Auto Parts Indonesia Cikarang Pusat with a sample of 80 employees. The method used is quantitative method. The data analysis used in this research is classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, t test and F test. The results of this study are motivation has a significant effect on employee performance on regression Y = 5.022 + 0.826 X1, a correlation value of 0.867 means that the two variables have a strong level of relationship. Work discipline has a significant effect on employee performance with the regression equation Y = 5.397 + 0.879 X2, the correlation value of 0.828 means that the two variables have a very strong level of relationship. Motivation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 3.125 + 0.565 (X1) + 0.339 (X2). The coefficient of determination is 77.3% and the rest is caused by other variables not examined in this study. The test results on the first hypothesis obtained the value of t count> t table or (15.355> 1.991). Based on the results of testing the second hypothesis, the value of t count> t table or (13.029> 1.991) is obtained. Based on the results of testing the third hypothesis, the value of F count > F table or ( 135.246 > 3, 12). This shows that simultaneously the variables of Motivation and Work Discipline have a significant influence on Employee Performance.